THE EFFECTIVENESS OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES AND DIGITAL RESOURCES IN IMPROVING THE QUALITY OF EDUCATION - Bozorov Zokir Yuldosh o’g’li (International Journal of Literature and Language Studies, 2026)
This research paper is dedicated to the issues of enhancing teaching quality in the modern educational system, improving student performance indicators, and integrating digital and innovative pedagogical technologies into the educational process. The aim of the study is to experimentally evaluate the impact of traditional teaching methods versus innovative (blended and project-based) learning methods on students' level of knowledge. A total of 240 students participated in the study, divided into control and experimental groups. The obtained results were verified using statistical analysis (t-test), revealing that the academic performance in the experimental group where innovative technologies were applied was 18.4% higher. The article develops scientific and practical recommendations for the strategic management of education quality and the systematic organization of quality monitoring.